Poligami dalam Perspektif Perjanjian Lama dan Implikasi Bagi Orang Kristen Masa Kini - Yolanda Raba Here (Jurnal Filsafat dan Teologi Katolik, 2023)
The practice of polygamy is a problem in the family that often occurs, in the Christian faith polygamy is in conflict with the principle of marriage. Family is God's creation since the beginning of the first human being, namely Adam and Eve. God first made humans a pair, so it is clear that in the event that the first humans had one husband and one wife, with this statement we can conclude that polygamy is not permitted by Christians and with polygamy is strictly prohibited in the Christian faith. The point of polygamy is to have more than one wife and that the Bible does not approve of polygamy happening. God does not approve of the marriage of more than one wife in Genesis 2:24 where it is very clear that a man will unite with his wife so that they become one flesh.